FROM SECULARISM TO THE POST-SECULAR: MODELS OF INTERACTION BETWEEN THE RELIGIOUS AND THE SECULAR IN CONTEMPORARY SOCIETY - Nargiza Aminova (Web of Journals Publishing, 2025)
The article examines the intellectual transition from classical secularism of the modern era to post-secular forms of religious–secular interaction in the 21st century. Drawing on the works of C. Taylor, H. Cox, B. Anderson, J. Habermas, H. de Vries and J. Casanova, it analyzes key concepts describing the transformation of religion under modernization, globalization and cultural pluralism. A comparative analysis is offered of national models of secularism. The study explores the formation of the post-secular condition. The findings are relevant for understanding contemporary religion–state relations and for analyzing societies in search of balanced models of secularism.
Keywords: (EN): Secularization; post-secularity; laïcité; Anglo-Saxon model; de-privatization of religion; Habermas; Taylor; religion and the public sphere.